2002
DOI: 10.1086/340250
|View full text |Cite
|
Sign up to set email alerts
|

Excess Infections Due to Antimicrobial Resistance: The “Attributable Fraction”

Abstract: Antimicrobial use causes a transient decrease in an individual's resistance to colonization by noncommensal bacteria ("competitive effect") and increases the likelihood of infection upon exposure to a foodborne pathogen. The additional "selective effect" of antimicrobial resistance results in a >3-fold increase in vulnerability to infection by an antimicrobial-resistant pathogen among individuals receiving antimicrobial therapy for unrelated reasons. Combining the increase in vulnerability to infection with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 16 publications
3
73
0
1
Order By: Relevance
“…The disease usually is associated with the consumption of undercooked poultry, particularly chicken (Shane 2000). Approximately 17 000 cases of Campylobacter infections per year have been recorded in the USA alone and most of them were antibiotic-resistant isolates (Barza and Travers 2002). A large proportion of commercial broiler chickens are colonized by campylobacters leading to high numbers of the pathogen on finished poultry products.…”
Section: Examples Of Applications Of Bacteriophage As a Biocontrol Agmentioning
confidence: 99%
“…The disease usually is associated with the consumption of undercooked poultry, particularly chicken (Shane 2000). Approximately 17 000 cases of Campylobacter infections per year have been recorded in the USA alone and most of them were antibiotic-resistant isolates (Barza and Travers 2002). A large proportion of commercial broiler chickens are colonized by campylobacters leading to high numbers of the pathogen on finished poultry products.…”
Section: Examples Of Applications Of Bacteriophage As a Biocontrol Agmentioning
confidence: 99%
“…41,42 Prolonged antimicrobial use can cause changes in gastro-intestinal flora and a decreased barrier to bacterial colonisation, facilitating Salmonella infection. 47,48 Bhan et al have found a significant association between the presence of serum antiHelicobacter pylori IgG antibodies and typhoid fever. 49 In a study in Vietnam, lower risk of typhoid was found to be associated with nucleotide polymorphisms in specific HLA alleles and the TNF-alpha promoter.…”
Section: Aetiologymentioning
confidence: 99%
“…In particular in children, in the elderly and in immunocompromised patients, however, the disease can be severe and effective antimicrobial treatment can be life saving. Another potential consequence of resistance is an increased incidence of salmonellosis in patients who, for unrelated reasons, are taking antimicrobials (Barza and Travers, 2002). …”
Section: Adverse Effects On Public Healthmentioning
confidence: 99%